2014
DOI: 10.1016/j.jda.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Suffix array and Lyndon factorization of a text

Abstract: The main goal of this paper is to highlight the relationship between the suffix array of a text and its Lyndon factorization. It is proved in [15] that one can obtain the Lyndon factorization of a text from its suffix array. Conversely, here we show a new method for constructing the suffix array of a text that takes advantage of its Lyndon factorization. The surprising consequence of our results is that, in order to construct the suffix array, the local suffixes inside each Lyndon factor can be separately proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 14 publications
1
54
0
Order By: Relevance
“…We refer to [6] where a new method is presented for constructing the suffix array of a text by using its Lyndon factorization advantageously. Partitioning the text according to its Lyndon properties allows tackling the problem in local portions of the text, local suffixes, prior to extending the solution globally, to achieve the suffix array of the entire text -the local portions are determined by the Lyndon factors.…”
Section: Applicationsmentioning
confidence: 99%
“…We refer to [6] where a new method is presented for constructing the suffix array of a text by using its Lyndon factorization advantageously. Partitioning the text according to its Lyndon properties allows tackling the problem in local portions of the text, local suffixes, prior to extending the solution globally, to achieve the suffix array of the entire text -the local portions are determined by the Lyndon factors.…”
Section: Applicationsmentioning
confidence: 99%
“…In [27,28], the authors found interesting relations between the sorting of the suffixes of a word w and that of its factors. Let w, x, u, y ∈ Σ * , and let u be a nonempty factor of w = xuy.…”
Section: Sorting Suffixes Of a Textmentioning
confidence: 99%
“…The suffix array (SA) of a word w is the lexicographically ordered list of the starting positions of the suffixes of w. The connection between Lyndon factorizations and suffix arrays has been pointed out in [17], where the authors show a method to construct the Lyndon factorization of a text from its SA. Conversely, the computation of the SA of a text from its Lyndon factorization has been proposed in [5] and then explored in [27,28].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Lyndon factorization has recently revealed to be a useful tool also in investigating queries related to sorting suffixes of a word, with strong potentialities for string comparison that have not been completely explored and understood [40,41]. Relations between Lyndon words and the Burrows-Wheeler Transform (BWT) have been discovered first in [13,38] and more recently in [32].…”
Section: Introductionmentioning
confidence: 99%